1990
DOI: 10.1093/clinchem/36.11.1922
|View full text |Cite
|
Sign up to set email alerts
|

Diet-related reference values for plasma amino acids in newborns measured by reversed-phase HPLC

Abstract: We have measured by reversed-phase HPLC concentrations of amino acids in plasma in groups of 80 normal appropriate-weight term babies fed from birth either a casein formula (WhiteCap SMA, n = 26), a whey formula (Gold Cap SMA, n = 26), or breast milk (n = 28). They were studied from day 11 to week 15 postpartum. The trend was towards an increase in amino acid concentrations in plasma with age, more marked in formula-fed than in breast-fed infants. Reference values were derived for each group. Both formula-fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…Plasma levels of Phe, therefore, are also higher in formula than in breast milk [ 7 ]. Phe and Thyroxine (Tyr) levels are up to 20% higher among formula-fed versus breast-fed infants [ 8 ]. These increases may be even higher in preterm infants, especially very preterm infants because of possible metabolic immaturity and the use of formulas with increased protein to allow extra weight gain to ensure normal growth [ 9 , 10 ], along with decreased catabolism of essential AA caused by formulas rich in casein, as seen for Phe and Tyr [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma levels of Phe, therefore, are also higher in formula than in breast milk [ 7 ]. Phe and Thyroxine (Tyr) levels are up to 20% higher among formula-fed versus breast-fed infants [ 8 ]. These increases may be even higher in preterm infants, especially very preterm infants because of possible metabolic immaturity and the use of formulas with increased protein to allow extra weight gain to ensure normal growth [ 9 , 10 ], along with decreased catabolism of essential AA caused by formulas rich in casein, as seen for Phe and Tyr [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cystine, glutamine, glycine, histidine, isoleucine, leucine, lysine, tryptophan, and valine showed increasing values throughout 0 to 18 years of age. Several other studies (20,28,29) have also reported a specific pattern of age-dependent amino acid concentrations with slight differences to Lepage et al's study. It seems that children under one year need specific reference value.…”
Section: Discussionmentioning
confidence: 58%
“…Previous published studies have quoted various ranges of target plasma AA and arginine concentrations for the VPN population based on different reference groups. Commonly used plasma arginine concentrations (mean ± SD) are from healthy term breast-fed infants with postnatal age between 28 and 32 days (95.3 ± 24.9 micromoles/L; range of 42.3–148.2 micromoles/L) 29 ; healthy term breast-fed infants with postnatal age of 11 days (55 ± 21 micromoles/L; range 11–88 micromoles/L) 30 ; preterm unsupplemented breast milk (69 ± 20 micromoles/L) 31 ; cord blood AA concentrations from neonates of 29 weeks’ gestation (82 ± 55 micromoles/L) 32 ; or low-birth-weight infants receiving TrophAmine (88.6 ± 40.6 micromoles/L) 33 . Reference plasma arginine concentrations range from a lowest value of 11 micromoles/L to a highest value of 148 micromoles/L.…”
Section: Introductionmentioning
confidence: 99%